The contribution of Jose Ortega y Gasset’s thinking on life in the contemporary philosophy - Costa, Edson Ferreira da (Argumentos - Revista de Filosofia, 2019)
This article unfolds the contribution of Jose Ortega y Gasset’s thinking, a Spanish philosopher who dedicated part of his work to think on issues related to human life and to propose a philosophical method called vital reason. Ortega’s concept of life is fundamental to engage in any reflective thinking proposed by the philosopher considering it as a key category in the process of understanding reality. From Nietzsche’s vitalism to Dilthey’s historicism, Ortega considers presenting his vital thought with originality by proposing a reflection that conceives life as an event, and this, as a personal reality. Accordingly, to understand this reality considered by him as radical implies to seize reason as an organ of understanding that is not restricted only to the process of scientific or philosophical theorization. The vital reason as a method helps the individual to understand himself within his life history, which is marked by innumerable contradictions.